1991
DOI: 10.1007/bf00114841
|View full text |Cite
|
Sign up to set email alerts
|

Learning automata from ordered examples

Abstract: Connectionist learning models have had considerable empirical success, but it is hard to characterize exactly what they learn. The learning of finite-state languages (FSL) from example strings is a domain which has been extensively studied and might provide an opportunity to help understand connectionist learning. A major problem is that traditional FSL learning assumes the storage of all examples and thus violates connectionist principles. This paper presents a provably correct algorithm for inferring any min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In Wiehagen (1976) CONS C IT LIM has been proved. Recent papers give new evidence for the power of iterative learning (Porat and Feldman 1988, Lange and Wiehagen 1991, Lange and Zeugmann 1992.…”
Section: The Inconsistency Phenomenonmentioning
confidence: 98%
“…In Wiehagen (1976) CONS C IT LIM has been proved. Recent papers give new evidence for the power of iterative learning (Porat and Feldman 1988, Lange and Wiehagen 1991, Lange and Zeugmann 1992.…”
Section: The Inconsistency Phenomenonmentioning
confidence: 98%
“…This is a more difficult problem, since it has been shown that learning is enhanced using lexicographic order in string presentation [56]. In practice, one cannot expect the training samples to be a complete ordered set, especially for unknown grammars.…”
Section: A Comparison With Rnnmentioning
confidence: 99%
“…Several are based on hypotheses that are not satisfied in the application domains, e.g., the presence of negative samples [5], the availability of teachers [12] or information on the order of the traces [13]. We developed our algorithm by extending the k-Tail algorithm and its many variants that work well on positive samples only [3,4,14] The GK-Tail algorithm proposed in this paper generates finite state automata augmented with parameters (FSAP) from sets of program traces in three steps.…”
Section: Synthesizing Models Of State-full Programsmentioning
confidence: 99%